2022
DOI: 10.1177/2156759x221134661
|View full text |Cite
|
Sign up to set email alerts
|

School Counselor and Administrator Perceptions of Response to the COVID-19 Pandemic

Abstract: Collaborative efforts by school counselors and school administrators that are grounded in social capital principles have the potential to better support students’ educational success, health, and well-being in the wake of challenging and adverse events, such as the COVID-19 pandemic. The purpose of this study was to assess perceptions of school counselors and administrators to determine the extent to which they had a shared vision of the challenges and strengths in their school’s initial response to the pandem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The school counselors expressed several professional challenges during the pandemic. Due to remote learning and school closures, they missed their traditional interactions with students and felt their relationships and engagement weakened; similar findings were also discussed by scholars examining school counselors' roles during the initial phases of the pandemic (Kruczek et al, 2022;Limberg et al, 2022). Related to other school counseling research (Limberg et al, 2022;Savitz-Romer et al, 2021;Villares et al, 2022), the school counselors in our study engaged in a multitude of ancillary or non-school-counseling roles (e.g., contract tracing, distributing technology, and long-term special education substitute teaching).…”
Section: Mirroring Shared Trauma and Posttraumatic Growthmentioning
confidence: 69%
See 1 more Smart Citation
“…The school counselors expressed several professional challenges during the pandemic. Due to remote learning and school closures, they missed their traditional interactions with students and felt their relationships and engagement weakened; similar findings were also discussed by scholars examining school counselors' roles during the initial phases of the pandemic (Kruczek et al, 2022;Limberg et al, 2022). Related to other school counseling research (Limberg et al, 2022;Savitz-Romer et al, 2021;Villares et al, 2022), the school counselors in our study engaged in a multitude of ancillary or non-school-counseling roles (e.g., contract tracing, distributing technology, and long-term special education substitute teaching).…”
Section: Mirroring Shared Trauma and Posttraumatic Growthmentioning
confidence: 69%
“…Educational/Societal-level Experiences. According to the literature, individuals from historically marginalized identities, including those who are BIPOC, have experienced greater systemic inequities in education, resources, and opportunities as a result of the pandemic (Hamilton & Ercikan, 2022;Kruczek et al, 2022). The school counselors in our study perceived similar trends, that the pandemic magnified inequities toward some school families, such as immigrant and undocumented families, who have greater job, home, medical, and food instability and lack of access; this study also highlighted school counselors' desire to address these systemic inequities.…”
Section: Mirroring Shared Trauma and Posttraumatic Growthmentioning
confidence: 99%
“…School counselors in the current COVID‐19 condition may have scored lower in multicultural competence than those in the pre‐COVID‐19 condition because the pandemic further exacerbated the lived experiences and challenges of low‐income families and students of Color (Huck & Zhang, 2021; Kruczek et al., 2022; Tillery et al., 2022). For example, Kruczek and colleagues (2022) found that school counselors’ reported challenges during the pandemic included effectively meeting the needs of historically marginalized students and students with special needs, as well as the limited help‐seeking behavior from the most vulnerable families. Other research also suggested that during the pandemic, school counselors have had limited access to students, traversed challenges with student engagement and motivation, and barriers to familial engagement such as technological issues and access to internet (Alexander et al., 2022; Huck & Zhang, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, our results indicated that participants in the pre‐COVID‐19 condition had higher scores on multicultural competence compared with their counterparts in the current COVID‐19 condition. School counselors in the current COVID‐19 condition may have scored lower in multicultural competence than those in the pre‐COVID‐19 condition because the pandemic further exacerbated the lived experiences and challenges of low‐income families and students of Color (Huck & Zhang, 2021; Kruczek et al., 2022; Tillery et al., 2022). For example, Kruczek and colleagues (2022) found that school counselors’ reported challenges during the pandemic included effectively meeting the needs of historically marginalized students and students with special needs, as well as the limited help‐seeking behavior from the most vulnerable families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation